Antecedent Factors of Green Purchasing Behavior: Learning Experiences, Social Cognitive Factors, and Green Marketing - Susanty, Aries; Puspitasari, Nia Budi; Prastawa, Heru; Listyawardhani, Pradhipta; Tjahjono, Benny (Frontiers in Psychology, 2021)
This study extends the Theory Planned Behavior (TPB) framework by introducing three further variables (learning experience, contextual factors, and green marketing) to explain how behavioral intention and actual behavior are induced by situational factors as well as green advertising from the company. Then, this study has four objectives. First, this study will assess the direct effect of personal factors (demographic factors) and contextual factors on learning experience and the direct effect of personal factors (demographic factors) on subjective norms. Second, this study will assess the direct effect of learning experience on social cognitive factors for a specific green product. Third, this study will assess the direct effect of social cognitive factors on intention purchasing behavior. Last, this study will assess the role of green marketing as moderating variable for the relationship between intention and purchasing behavior. Data used in this study were primary data which were collected through closed questionnaires with a 1-5 Likert scale. This study succeeded in obtaining 602 valid data from the results of filling out questionnaires by participants. This study uses the partial least square (PLS) method with SmartPLS 3.0 for data processing. The result of data processing indicated that outcome expectation, self-efficacy, and subjective norms had significant positive effects on purchase intention for green personal care products. This study also found that the learning experience influenced both outcome expectation and self-efficacy. Although weak, the learning experience was influenced by demographic factors and contextual factors. The demographic factors that affect learning experience were gender and level of education. The contextual factor has a more substantial influence on learning experience in developing consumption-related attitudes to green personal care products than the demographic factor. Finally, this study also found the direct effect of intention on actual purchase behavior and the positive role of green marketing as the moderating variable